The Necessity of Ambiguity in Self–Other Processing: A Psychosocial Perspective With Implications for Mental Health - de Bézenac, Christophe Emmanuel; Swindells, Rachel Ann; Corcoran, Rhiannon (Frontiers in Psychology, 2018)
While distinguishing between the actions and physical boundaries of self and other (non-self) is usually straightforward there are contexts in which such differentiation is challenging. For example, self–other ambiguity may occur when actions of others are similar or complementary to those of the self. Even in the absence of such situational challenges, individuals experiencing hallucinations have difficulties with this distinction, often experiencing thoughts or actions of self as belonging to other agents. This paper explores the role of ambiguity in self–other differentiation, drawing from developmental, psychodynamic, and neurocognitive perspectives. A key proposal is that engagement in contexts that make distinctions between self and other challenging yet necessary allow reality-testing skills related to agency to develop. Attunement in typical caregiver–infant interactions is framed as a safe but inherently ambiguous environment that provides optimal condition for the infant to develop a coherent self–other sense. Vulnerability to psychosis may be related to limited access to such an environment in early development. However, the perceptual, cognitive, and social skills that contribution to attribution are likely to be malleable following infancy and improve though opportunities for boundary play in similarly ambiguous settings. Using music-making to illustrate, we postulate that engagement in intricate joint-actions that blurs agentic boundaries can contribute to the continued development of an adaptive sense of self and other essential to healthy social functioning. Increased insight into the self–other ambiguity may enhance our understanding of mechanisms underlying “self-disorders” such as schizophrenia and eventually extend the range of social and arts-based therapeutic possibilities.